Coherent diffraction radiation interferometry and short bunch length measurements - Potylitsyn A. P. Alexander Petrovich (2005, 2005)
The promising approach to measure a length of subpicosecond electron bunch is connected with measurements of coherent diffraction radiation (CDR) spectra due to strong dependence of the spectrum shape on the bunch length oz in the wavelength region oz [Proceedings of the International Symposium on New Visions in Laser-Beam Interactions, Nucl. Instr. and Meth. A 455 (1) (2000)]. The spectral measurements may be carried out by using an interferometer or a polychromator.